Conociendo las partes de la planta - Figueroa Cochachin, Martha Elizabeth (2018)
It is very important that the students of initial education have basic knowledge about the plants, that is, the main parts like: the root, the stem, the leaves, seeds and fruits, likewise, it is important that they know the functions that each of these meets and performs in relation to the plant by reason of its own existence and also in terms of the benefit achieved by man on a daily basis, with the multiple uses that are given to the parts of the plants, since they not only they provide us with purified air, but they also contribute enormously to the fact that life on planet earth is healthy and sustainable.